2013
DOI: 10.1002/chem.201203963
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of Oligovalent β‐(1→2)‐Linked Oligomannosides: New Insights into Carbohydrate‐Based Adjuvants in Immunotherapy

Abstract: A series of oligovalent carbohydrate assemblies (ranging from mono- to pentavalent), derived from three structurally different β-linked or β-(1→2)-linked mannosides, has been chemically synthesized, and the respective compounds have been biologically evaluated in order to investigate their immunostimulatory properties. The Crich methodology for β-mannosylation was successfully utilized to introduce the β-linkages, and a click chemistry protocol was utilized to generate the oligovalent derivatives. A convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…The target pentasaccharide as its 2-aminoethyl glycoside 1 was synthesized using a set of stereoselective glycosylations of a number of suitably functionalized monosaccharide derivatives 2 , 3 [14], 4 , 5 [15], 6 [16] and 7 [17], which were prepared from the commercially available reducing monosaccharides using a number of functional group manipulations reported earlier (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The target pentasaccharide as its 2-aminoethyl glycoside 1 was synthesized using a set of stereoselective glycosylations of a number of suitably functionalized monosaccharide derivatives 2 , 3 [14], 4 , 5 [15], 6 [16] and 7 [17], which were prepared from the commercially available reducing monosaccharides using a number of functional group manipulations reported earlier (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Triacedimannose is a trivalent glycocluster, consisting of fully acetylated β‐(1→2)‐linked mannobiose units, designed to mimic C. albicans cell wall mannan oligosaccharides, which are known to possess immunostimulatory properties . We have earlier shown in vitro that TADM beneficially affects cytokine production of peripheral blood cells among allergic subjects and favours T helper 1 and T regulatory cell type responses . Previously, we have also shown that, in contrast to CpG and MPLA, TADM does not appear to function as TLR agonist .…”
Section: Discussionmentioning
confidence: 99%
“…One dosage (50 μL) contained 10 000 SQ (5 μg different timothy allergens of which 2 μg was a major allergen (Phl p 5)). Triacedimannose (1,2,3‐Tris{1‐[(2,3,4,6‐tetra‐ O ‐acetyl‐β‐D‐mannopyranosyl)‐(1→2)‐(3,4,6‐tri‐ O ‐acetyl‐α‐D‐mannopyranosyloxyethyl)]‐4‐(methyl‐1‐oxy)‐1,2,3‐triazolyl}propane) (Figure ) was synthesized as previously described . CpG and synthetic MPLA were purchased from InvivoGen (San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Lin’s group demonstrated thiotolyl mannoside could be coupled with a 6-azidohexyl linker under the activation of NIS/TfOH at low temperature to afford α-6-azidohexyl manoside in good yield [ 83 ] ( Figure 12 , entry 7). On the other hand, a more challenging β-azidoethyl mannoside was synthesized by Leino’s group using Crich’s modified pre-activation [ 84 ] method, which required very careful temperature control [ 85 ] ( Figure 12 , entry 8). Although the yield of the desired product was only 34%, the applicability of this methodology to disaccharide thioglycoside donors is notable.…”
Section: Stereoselective Anomeric Functionalization For Chemical Cmentioning
confidence: 99%